USE OF SUITABLE EQUATION OF STATE FOR THE CONVERSION OF VOLUMETRIC TO MASS FLOWRATE IN NGV REFUELING MEASUREMENT - Abdul Mutalib, M I (Institution of Engineers, Malaysia, 2009)
Natural Gas Vehicle (NGV) is not new in the industry; however, it is becoming an uprising issue owing to the multitude advantages natural gas posses compared to the conventional fuel. The challenges, on the other hand, are putting in place an NGV refueling facility and keeping the cost of natural gas operated vehicles competitive with conventional vehicles. One of the identified cause for the dearly NGV refueling station installation cost is the mass measurement device, Coriolis flow meter, used in each station. This research is aimed at finding and implementing a cost effective alternative to the Coriolis flow meter. A typical volumetric flow meter i.e., turbine, orifice and vortex is much lower in price but does not produce measurement in the natural gas trading unit. To compensate for this, a conversion tool based on an Equation of State (EOS) is developed. In this method, mass flowrate of natural gas is calculated using the volumetric flowrate measured by volumetric flow meter, whilst temperature and pressure of the flowing gas are fed into the conversion tool. Based on results, it is found that the developed conversion tool is able to compute the mass flowrate of natural gas with reasonably average error which is 2.66% compared to the actual measurement using Coriolis flowmeter.